ADSORPSI METHYLENE BLUE OLEH ARANG AKTIF BIJI BUAH LAI (DURIO KUTEJENSIS) - Mulyana -; Teguh Wirawan; Eva Marliana (JURNAL ATOMIK, 2025)
The research on the adsorption of methylene blue dye by activated charcoal of lai fruit seeds has been conducted. The purpose of this study was to determine the optimum pH and time as well as the maximum adsorption capacity and isotherm type (Langmuir and Freundlich) of activated charcoal of lai fruit seeds in adsorbing methylene blue dye. In this study, activated charcoal was made through a carbonation process at a temperature of 500 oC for 4 hours and was chemically activated by soaking in 2 M HCl for 24 hours. Characterization of activated charcoal was carried out using water content test, ash content, Fourier Transform Infrared (FTIR) spectrum analysis, and Scanning Electron Microscopy (SEM). In lai seed charcoal, the water content value was 8.97% and in lai seed activated charcoal it was 8.27%, the ash content was 0.16% in lai seed charcoal and 0.09% in lai seed activated charcoal. The surface area of lai seed charcoal and lai seed activated charcoal obtained values of 72.201 m²/g and 80.230 m²/g respectively. The results of the FTIR spectra on lai seed activated charcoal showed the presence of C-H (1426.21 cm-1), C=C (1591.65 cm-1), C=O (1690.06 cm-1), O-H (3320.22 cm-1). Based on the results of SEM on lai seed charcoal, the particle surface looks rough and uneven, and has pores and a larger surface area. The adsorption of methylene blue follows the Freundlich isotherm model. The methylene blue adsorption test showed an optimum pH at 8, and an optimum time of 45 minutes with a maximum adsorption capacity of 32.69 mg/g.